Effect of vegetable oil (Brazil nut oil) and mineral oil (liquid petrolatum) on dental biofilm control - Cíntia de Fátima Buldrini Filogônio; Rodrigo Villamarim Soares; Martinho Campolina Rebello Horta; Cláudia Valéria de Sousa Resende Penido; Roberval de Almeida Cruz (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Dental biofilm control represents a basic procedure to prevent caries and the occurrence of periodontal diseases. Currently, toothbrushes and dentifrices are used almost universally, and the employment of good oral hygiene allows for appropriate biofilm removal by both mechanical and chemical control. The aim of this study was to evaluate the effectiveness of adding vegetable or mineral oil to a commercially available dentifrice in dental biofilm control. A comparison using the Oral Hygiene Index Simplified (OHI-S) was performed in 30 individuals who were randomly divided into three groups. Group 1 (G1) received a commercially available dentifrice; the composition of this dentifrice was modified by addition of mineral oil (Nujol®) for group 2 (G2) or a vegetable oil (Alpha Care®) for group 3 (G3) at 10% of the total volume, respectively. The two-way repeated-measures analysis of variance (two-way ANOVA) was used to test the effect of group (G1, G2 and G3) or time (baseline, 45 days and 90 days) on the OHI-S index scores. Statistical analysis revealed a significant reduction in the OHI-S at day 90 in G2 (p < 0.05) and G3 (p < 0.0001) in comparison to G1. Therefore, the addition of a vegetable or a mineral oil to a commercially available dentifrice improved dental biofilm control, suggesting that these oils may aid in the prevention and/or control of caries and periodontal disease.